The Influence of Product Quality and Service Quality on Customer Satisfaction of Sandy Honey Grilled Chicken Lampung Branch - Kenko Gunawan, Kangsen; Tiara Narundana, Vonny (International Journal of Social Science, Education, Communication and Economics, 2024)
Sales of Sandy Cab Honey Grilled Chicken. Lampung every month is uncertain and causes income to become unstable. The research carried out examines the impact of product and service quality on the level of customer satisfaction at that location. For the purposes of this research, a quantitative methodology was used by taking a sample consisting of 100 customers of Ayam Bakar Madu Lampung branch, using a sampling technique based on the Lemeshow formula. Data analysis was carried out with the help of SPSS software, including various statistical tests to assess validity, reliability, and using coefficient of determination testing, multiple linear regression, F test, and T test. The results of the research indicate that: 1) Product quality has a significant impact on consumer satisfaction at Ayam Bakar Honey Lampung branch. Similarly, 2) Service quality was found to have a significant effect on customer satisfaction, which confirms the importance of, 3) Product quality and Service quality on the level of consumer satisfaction in the restaurant.